Association between sleep disorders and subsequent heart failure - Jamschid Sedighi; Mark Luedde; Julia Gaensbacher-Kunzendorf; Hans-Joerg Hippe; Pascal Bauer; Birgit Assmus; Samuel Sossalla; Karel Kostev (International Journal of Cardiology: Heart & Vasculature)
Background: Sleep disorders are prevalent conditions that may influence the progression of various heart diseases. However, the relationship between sleep disorders and the onset of heart failure (HF) remains unclear. Objective: The purpose of this study was to investigate whether sleep disorders are associated with an increased risk of developing HF. Methods: We conducted a retrospective cohort study using data from 1,293 general practices across Germany sourced from the IQVIA Disease Analyzer database. The study included patients with an initial diagnosis of HF (ICD-10 code: I50) between January 2010 and December 2022 (index data) These patients were matched with control subjects without HF based on age, sex, and pre-existing conditions. The primary outcome was the association between prior sleep disorder diagnoses and the subsequent development of HF. Data were available for 9,345,246 individuals, of which 406,265 had a history of HF. Results: The study analyzed data from 123,516 patients with HF and an equal number of matched controls. The mean age of participants was 73.3–73.4 (SD 12.4) years, with 53.2% being women. Sleep disorders diagnosed prior to the onset of HF were significantly associated with an increased risk of developing HF. This association was consistent across different types of sleep disorders overall (OR: 1.22; 95%CI: 1.19–1.24) as well as insomnia (OR: 1.26; 95%CI: 1.21–1.31), sleep apnea (OR: 1.20; 95%CI: 1.15–1.25), and unspecified sleep disorders (OR: 1.21; 95%CI: 1.18–1.25). Conclusion: In this large cohort of outpatients, a prior diagnosis of sleep disorders was linked to a higher incidence of HF. These findings suggest that sleep disorders may serve as a risk factor for the development of HF, highlighting the need for early identification and management of sleep disturbances in at-risk populations. Addressing these disorders in clinical practice could represent a pivotal step towards better cardiovascular health and patient care.